Investigation of the influence of wear in impeller seals on the axial force in double suction pumps. Issue 1 (March 2020) - Isaev, N; Budaev, G; Danilov, D; Dobrokhodov, K
Abstract: This article is devoted to the investigation of axial force on the rotor of the double suction centrifugal pump at unequal wear of impeller seals. The annular seal of the double suction centrifugal pump is considered as an object of the study. The distribution of the fields of velocities and pressure in the seals of the pump are obtained by numerical modeling. The leakage rate resulting from the simulation is compared to the existing formulas.